Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pengungkapan Wajib dalam Laporan Keuangan Pemerintah Daerah Kabupaten/Kota di Indonesia - Putri Halimatussya’diah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study examines the factors that influence the level of mandatory disclosure in local government financial statements in Indonesia. The independent variables in this study is regional wealth, capital expenditure, and transfer revenue. The research population comprises 507 district and city across Indonesia for the 2024 period. The sample was selected using a purposive sampling method, obtain total of 345 local government financial statements that met the established sampling criteria for testing purposes. The analytical technique employed in this study is multiple linear regression using SPSS 25. The results indicate that all independent variables namely regional wealth, capital expenditure, and transfer revenue have a significant influence on the level of mandatory disclosure in local government financial statements. Regional wealth and transfer revenue exhibit a positive effect on the dependent variable. Therefore, the hypotheses for both variables are supported. In contrast, capital expenditure in this study demonstrates a negative effect on the dependent variable, resulting in the rejection of its corresponding hypothesis. This study further reveals that the average level of mandatory disclosure fulfilled by local governments stands at only 26%.